Variability assessment in SOC stocks influenced by different cropping systems and landuse using Geographic Information Systems (GIS) techniques in Chittoor district of Andhra Pradesh - MOHAN, M. MADHAN; PRASAD, T.N.V. K.V.; MADHURI, K.V. NAGA (Journal of Soil and Water Conservation, 2020)
The soil organic carbon (SOC) plays a pivotal role in soil biodiversity, nutrient and water recycling,agricultural productivity and sustainability of land use and cropping systems through climate changemitigation and adaptation. The main objective of current study is to assess the variability influenced byexisting major land use and cropping systems of the Chittoor district during 2018. The study area locatedbetween 12°37’ to 14°08’ N latitude and 78°03’ to 79°55’ E longitude. The major land use and croppingsystems identified were rice based cropping system, sugarcane based cropping system, vegetable basedcropping system, groundnut based cropping system, casuarina and eucalyptus plantations, mangoorchards, mulberry based cropping system, Perennial fodder crops, flower crops, forest land use, fallowand waste land use etc. Soil organic C content was highest under forest land use (10.0 g kg-1) followed bypaddy-tomato (9.9 g kg-1), mango orchards >15 years (9.2 g kg-1), eucalyptus plantations (9.2 g kg-1) andsugarcane-vegetable (9.0 g kg-1). Similarly, carbon sequestration rate was highest in forest land use (28.2Mg ha-1) followed by mango orchards >15 years age (21.1 Mg ha-1), sugarcane-vegetables (20.4 Mg ha-1)and paddy-tomato (19.9 Mg ha-1) cropping systems. The organic carbon status was very low (0.2-0.4%)in rainfed groundnut, current fallows and sugarcane-sugarcane cropping systems; medium (0.6-0.8%)in mango0.8%) insugarcane-vegetables, forest land use, paddy-tomato, mango >15 yrs and perennial fodder plantations.